High-grade energy compensation ratio in a conventional subcritical vapour-compression heat-pump cycle. (25th June 2018) - Qv, Dehu; Wang, Jijin; Shang, Runxin; Ni, Long; Yao, Yang
Highlights: The concept of high-grade energy compensation (HGEC) has been developed and derived. HGEC is helpful for better understanding and assessing the high-grade energy-use efficiency. All derivations are suitable for conventional subcritical vapour-compression heat-pump cycles. COP and/or EER tend to overestimate the high-grade energy-use efficiency. Abstract: The concept of high-grade energy compensation (HGEC) has been developed and derived based on thermodynamic analysis for better understanding and assessing the high-grade energy-use efficiency in a conventional subcritical vapour-compression heat-pump (VCHP) cycle. The derivation proposes a lower limit of HGEC ratio in a conventional subcritical VCHP cycle, meaning that the COP and/or EER that we get used to employing for assessing energy efficiency tend to overestimate the high-grade energy-use efficiency.